Effect of 1-Methyl-2-Mercapto-5-(3-Pyridyl)-Imidazole (KC-6141) on Rabbit Platelet Aggregation in Vitro and Rat Platelet Retention - Umetsu, Teruhiko; Kato, Tadakatsu (Thrombosis and Haemostasis, 1978)
Effect of l-methyl-2-mercapto-5-(3-pyridyl)-imidazole (KC-6141) on rabbit platelet aggregation in vitro and rat platelet retention were investigated.In the in vitro study, KC-6141 inhibited ADP-induced aggregation by 27% at 5× 10−4M, being more active than dipyridamole but much less than adenosine. Inhibition of arachidonic acid-and collagen-induced aggregation by KC-6141 was more effective than that of ADP-induced one and its ED50 was 2.1×10−5 and 8×10−5M, respectively. KC-6141 was 10 and 4 times more potent than aspirin in arachidonic acid-and collagen-induced aggregation, respectively. The dose-response curve of KC-6141 was parallel to that of aspirin, suggesting it is an aspirin-like compound.In the platelet retention study, a method for determining platelet retention in rats was devised so that platelet retention can be measured with a volume of blood as small as possible. By use of the method, effects of KC-6141, aspirin and dipyridamole were compared. When administered intraperitoneally at 100 mg/kg, KC-6141 indicated 54.8% inhibition of platelet retention, whereas aspirin and dipyridamole showed only 23.5 and 5.2% inhibition, respectively. On the oral administration at 200 mg/kg, KC-6141 inhibited by 60.8% and its ED50 was 125 mg/kg. The activity lasted over 32 hr.The above results demonstrated that KC-6141 is a compound with more potent action on the platelet aggregation, as well as on the platelet retention than aspirin and dipyridamole – a known antithrombotic drug.